Use of essential trace elements enriched Artemia in the larval rearing of barramundi (Lates calcarifer) - Fehér, Milán; Bársony, Péter; Baranyai, Edina; Posta, József; Stündl, László (Acta Agraria Debreceniensis, 2012)
Artemia is a vital nutriment in the rearing of barramundi (Lates carcarifer), however it’s mineral trace element content does not cover the requirements of the larvae. In our experiment the assumption was wether the cobalt, zinc and manganese concentration of Artemia could be increased during a 24 hours of enrichment period, as well as we wanted to investigate the resulted interactions between the elements. For this purpose 50, 100 and 1000 mg l-1 cobalt-chloride treatements (Co50, Co100, Co1000) were applied while in the case of 50 and 100 mg l-1 treatments the enrichment was also complemented with zink-sulphate and manganese-chloride in the same concentrations. According to the results the zooplankton were able to accumulate cobalt in higher amount, and yet zinc and manganese had no significant effect on each other, a strong synergistic effect occurred between cobalt and manganese. After the enrichment period the impact of essential trace element supplemented live feed on the survival and growth of barramundi larvae was also studied. The experiment was carried out by using 15 days-old larvae applying a total of 9 treatments for two weeks (Control, Co50, Co100, Mn50, Mn100, CoZn50, CoZn100, CoMn50, CoMn100), in duplicates. Considering the per cent of survivals, no significant difference was observed between the treatements (P>0.05). In the case of CoMn50 and CoMn100, the loss statistically increased (P<0.05) compared to the Control (80.5±4.95%) group. Our results show, that the Mn100 and CoMn100 treatements resulted in ignificantly higher (P<0.05 ) in divid ual bod y w eight s, how ever taki ng the survival also into consideration the Mn100 treatements proved to be the most effective.